Characterization, comparative phylogenetic, and gene transfer analyses of organelle genomes of Rhododendron × pulchrum - Shen, Jianshuang; Li, Xueqin; Li, Mingzhi; Cheng, Hefeng; Huang, Xiaoling; Jin, Songheng (Frontiers in Plant Science, 2022)
Rhododendron × pulchrum, an important horticultural species, is widely distributed in Europe, Asia, and North America. To analyze the phylogenetic and organelle genome information of R. × pulchrumR. × pulchrum and its related species, the organelle genome of R. × pulchrum was sequenced and assembled. The complete mitochondrial genome showed lineage DNA molecules, which were 816,410 bp long and contained 64 genes, namely 24 transfer RNA genes, 3 ribosomal RNA genes, and 37 protein-coding genes. The chloroplast genome of R. × pulchrum was reassembled and re-annotated; the results were different from those of previous studies. There were 42 and 46 simple sequence repeats identified from the mitochondrial and chloroplast genomes of R. × pulchrum, respectively. Five genes (nad1, nad2, nad4, nad7, and rps3) were potentially useful molecular markers. The R. × pulchrum mitochondrial genome collinear alignment among five species of the Ericaceae showed that the mitochondrial genomes of these related species have a high degree of homology with R. × pulchrum in this gene region, and the most conservative genes were trnC-GCA, trnD-GUC, trnM-CAU, trnN-GUU, trnY-GUA, atp4, nad4, nad2, nad5, ccmC, and rrn26. The phylogenetic trees of mitochondrial genome showed that R. simsii was a sister to R. × pulchrum. The results verified that there was gene rearrangement between R. × pulchrum and R. simsii mitochondrial genomes. The codon usage bias of 10 Ericaceae mitochondrial genes and 7 Rhododendron chloroplast genes were influenced by mutation, while other genes codon usages had undergone selection. The study identified 13 homologous fragments containing gene sequences between the chloroplast and mitochondrial genomes of R. × pulchrum. Overall, our results illustrate the organelle genome information could explain the phylogenetics of plants and could be used to develop molecular markers and genetic evolution. Our study will facilitate the study of population genetics and evolution in Rhododendron and other genera in Ericaceae.